2016
DOI: 10.1038/ncomms13794
|View full text |Cite
|
Sign up to set email alerts
|

Zinc isotope evidence for sulfate-rich fluid transfer across subduction zones

Abstract: Subduction zones modulate the chemical evolution of the Earth's mantle. Water and volatile elements in the slab are released as fluids into the mantle wedge and this process is widely considered to result in the oxidation of the sub-arc mantle. However, the chemical composition and speciation of these fluids, which is critical for the mobility of economically important elements, remain poorly constrained. Sulfur has the potential to act both as oxidizing agent and transport medium. Here we use zinc stable isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 54 publications
4
61
1
1
Order By: Relevance
“…A generally positive correlation between fO 2 and fluid input has been observed in primitive arc basalts in previous studies (Bénard et al, ; Brounce et al, , ; Debret et al, ; Evans, ; Evans & Tomkins, ; Kelley & Cottrell, ; Pons et al, ; Rielli et al, ), and thus, fluid influx was proposed as the cause of mantle wedge oxidization. V/Ti ratios in ophiolites (Shervais, ) and basalts (Woodhead et al, and this study) can be used to record fO 2 in their mantle sources.…”
Section: Discussionmentioning
confidence: 59%
“…A generally positive correlation between fO 2 and fluid input has been observed in primitive arc basalts in previous studies (Bénard et al, ; Brounce et al, , ; Debret et al, ; Evans, ; Evans & Tomkins, ; Kelley & Cottrell, ; Pons et al, ; Rielli et al, ), and thus, fluid influx was proposed as the cause of mantle wedge oxidization. V/Ti ratios in ophiolites (Shervais, ) and basalts (Woodhead et al, and this study) can be used to record fO 2 in their mantle sources.…”
Section: Discussionmentioning
confidence: 59%
“…Crustal recycling and melt percolation are crucial for the chemical evolution of the mantle (e.g., Bodinier & Godard, ). Previous studies have shown that recycling of isotopically heavy subducted slab‐derived components (e.g., carbonate melts and/or fluids) can dramatically modify the Zn isotopic composition of the upper mantle (Liu et al, ; Pons et al, ; Wang et al, ). However, the behavior of Zn isotopes during melt percolation has been not yet known, which significantly hampers the application of Zn isotopes to understand mantle geochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Subduction zones are the primary locations for the global sulfur cycle, transporting sulfur to the deep mantle via the descending slab or returning it to the surface by arc magmatism 2,4,5 . Compared to fresh MORB, the relatively high sulfur concentrations ([S], up to 3000 µg g −1 ) and positive δ 34 S values (+5 to +11‰) of volcanic rocks and melt inclusions in some arcs (e.g., Western Pacific) [4][5][6][7] , and the presence of sulfate in mantle xenoliths 8 , have been attributed to the addition of slab-derived sulfate to arc magmas by fluids 8,9 . Alternatively, some deep arc cumulates (e.g., Eastern Pacific) with mantle-like δ 34 S values suggest more limited slabderived sulfate contributions to arc lavas and that the positive δ 34 S signature of the lavas results from crustal assimilation 10 .…”
mentioning
confidence: 99%
“…Experimental results suggest that slab-derived aqueous fluids are an effective agent for transporting sulfur from the slab to the mantle wedge 11,12 . In addition, some studies predict that sulfates are likely the dominant sulfur species in slab-derived fluids 9,13 . On the other hand, sulfate is relatively rare in high-pressure (HP) rocks [13][14][15][16][17][18] , and experimental studies have proposed that reduced sulfur species are dominant in slab fluids 11 .…”
mentioning
confidence: 99%